(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The objective of this research is to define the international standards of the Supreme Audit Institutions (INTOSAI), which regulate the work of the SAIs and the management of their functions and responsibilities. It also aims at detailing the international standards of the Supreme Audit Institutions, Subject to his control . In order to achieve the objectives of the research, a questionnaire was designed which included many questions that were addressed to a number of officials and employees of the Federal Audit Bureau and its affiliated bodies regarding the extent to which the international standards of SAIs are applied . The research found a number of conclusions, the most important of which is that there is a shortage in the number and content of the audit evidence issued by the Federal Audit Office in Iraq compared to the number and content of the international standards of the Supreme Audit Institutions issued by INTOSAI, as there is slow progress and very limited to the development of the audit evidence issued In accordance with the latest developments of the local environment compared to the international standards of the Supreme Audit Institutions, which are subject to constant modification and development. The research also presented a set of recommendations, the most important of which was the urging of officials in the Federal Audit Bureau, The representative of the SAI in the Board of Accounting and Auditing Rules and Standards in Iraq should comply with the international standards of the Supreme Audit Institutions or adopt them.